CTA bridges the gap between researchers and producers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Information should be dissiminated with the end-user In mind. Ease of access to scientific and technical information (STI), is one of the main concerns of those working in development today. In order to bridge the gap between research and fieldwork...